Envisioning action‐oriented and justice‐driven climate change education: Insights from youth climate justice activists - Trott, Carlie D. (Children & society, 2024)
Through in‐depth interviews, this study explored US youth climate justice activists' views and experiences of climate change education (CCE) and their recommendations for alternative educational approaches to advance climate justice. Youth activists (N = 16; ages 15 to 17) viewed education as critical to spurring societal transformation, however, most described narrowly focused (e.g., depoliticized; science‐centric) or inadequate (e.g., sparse, absent) school‐based CCE. Youths' recommendations emphasized the need for justice‐driven and action‐oriented CCE for all ages to equip all learners with the knowledge and skills to actively contribute to urgently needed, justice‐minded, systems‐level change. Findings have implications for curricular and policy change that enable education for climate justice action.